ISOLASI DAN KARAKTERISASI UMUM MIKROBA YANG DIDUGA ENTEROBACTERIACEAE PADA JAJANAN DI WILAYAH PURWOKERTO MENGGUNAKAN MEDIUM EMBA - Neli Oktaviani; Indah Sulistiyawati; Nur Laila Rahayu (Scientific Timeline, 2022)
One of the foods that people often consume is street food. Street snacks are often an intermediary for the spread of disease due to the contamination of pathogenic microorganisms. One of the pathogenic microorganisms that can cause disease in humans is Escherichia coli bacteria. This study identified the presence of Enterobacteriaceae pathogen bacteria in roadside snacks in the Purwokerto area, Banyumas Regency. This research is a qualitative descriptive study with a purposive sampling method. The roadside snacks used in this study were snacks with fish-based ingredients, namely dumplings, meat-based ingredients, meatballs, and snacks with egg-based ingredients, namely egg rolls. Snack samples were tested by dilution to a level of 10-5 and inoculated into a dish containing EMBA media. Identification of Enterobacteriaceae bacteria was carried out by observing colony morphology, several colonies, and gram staining. The results obtained showed that 9 out of 18 samples were positively contaminated with Escherichia coli bacteria. The sample that contains the most Enterobacteriaceaebacteria is the sample with the basic ingredient of fish, namely siomay code S PU A1 with the number of colonies 15x1065.